The Effect of Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) And Non-Performing Loans (NPL) on Return on Asset (ROA) In Banking Companies Listed on The Indonesia Stock Exchange During The Period Of 2016-2020 - Tami, Sri Utami Permata; Riska Kumala Dewi (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This study aimed to determine the partial and simultaneous effect of Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) and Non-Performing Loans (NPL) on Return On Asset (ROA) in banking companies shares listed on the Indonesia Stock Exchange in 2016-2020. The population of this study were all conventional commercial banking companies listed on the Indonesia Stock Exchange in the period of 2016-2020.The sampling technique was carried out by purposive sampling, so that 9 banking companies were obtained as study samples. The data analysis technique used was linear regression analysis by Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) and Non-Performing Loans (NPL) as independent variable and Return On Asset (ROA) as the dependent variable. The results of this study indicated that Capital Adequacy Ratio (CAR) partially had a significant and positive effect on Return On Asset (ROA), Loan To Deposit Ratio (LDR) had no significant and positive effect on Return On Asset (ROA), and Non-Performing Loans (NPL) had no significant and negative effect on Return On Asset (ROA). While Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) and Non-Performing Loans (NPL) simultaneously had a significant effect on Return On Asset (ROA).